Vertical bone augmentation and regular implants versus short implants in the vertically deficient posterior mandible: a systematic review and meta-analysis of randomized studies. Issue 9 (September 2021) - Terheyden, H.; Meijer, G.J.; Raghoebar, G.M.
Abstract: The aim of this study was to perform a systematic review and meta-analysis of randomized controlled trials (RCTs) comparing the outcomes of short dental implants (≤7 mm) versus vertical bone augmentation followed by regular dental implants (>7 mm) in the deficient posterior mandible. In total, eight RCTs (six using interpositional sandwich grafting and two using a guided bone regeneration technique) were reported in 17 articles at different time points. In the meta-analysis of the sandwich group, the relative risk (RR) for implant loss at 1 year was in favour of short implants (RR 0.41, P  = 0.02), while no significant difference was found at 3 years (RR 0.65, P  = 0.43), 5 years (RR 1.08, P  = 0.86), or 8 years (RR 1.53, P  = 0.52). The risk of complications was in favour of short implants (RR 0.34, P  = 0.0002), as was the mean difference in marginal bone resorption after 1 year (−0.09 mm, P  = 0.17), 3 years (−0.32 mm, P  < 0.00001), 5 years (−0.65 mm, P  < 0.00001), and 8 years (−0.88, P  < 0.00001). The mean residual osseointegration length of the implants was between 2.94 mm and 4.44 mm in the short implants group and between 7.97 mm and 8.62 mm in the regular implants group after 5 years. In conclusion, in the deficient atrophic posterior mandible, short implants and regular implants demonstrate comparable outcomes within the first 5 years. Patients who are fit for surgery should be informed about the risks and benefits of both options.